Synthesis and Biological Evaluation of 99mTc(I) Tricarbonyl Complexes Dual-Targeted at Tumoral Mitochondria - Diogo Figueiredo; Célia Fernandes; Francisco Silva; Elisa Palma; Paula Raposinho; Ana Belchior; Pedro Vaz; António Paulo (Molecules, 2021)
For effective Auger therapy of cancer, the Auger-electron emitters must be delivered to the tumor cells in close proximity to a radiosensitive cellular target. Nuclear DNA is considered the most relevant target of Auger electrons to have augmented radiotoxic effects and significant cell death. However, there is a growing body of evidence that other targets, such as the mitochondria, could be relevant subcellular targets in Auger therapy. Thus, we developed dual-targeted 99mTc(I) tricarbonyl complexes containing a triphenylphosphonium (TPP) moiety to promote accumulation of 99mTc in the mitochondria, and a bombesin peptide to provide specificity towards the gastrin releasing peptide receptor (GRPr) overexpressed in prostate cancer cells. The designed dual-targeted complex, 99mTc-TPP-BBN, is efficiently internalized by human prostate cancer PC3 cells through a specific GRPr-mediated mechanism of uptake. Moreover, the radioconjugate provided an augmented accumulation of 99mTc in the mitochondria of the target tumor cells, most probably following its intracellular cleavage by cathepsin B. In addition, 99mTc-TPP-BBN showed an enhanced ability to reduce the survival of PC3 cells, in a dose-dependent manner.